1998
DOI: 10.1103/physrevlett.81.3100
|View full text |Cite
|
Sign up to set email alerts
|

Beta Decay of6874Niand Level Structure of Neutron-Rich Cu Isotopes

Abstract: The isotopes 68 74 Ni, of interest both for nuclear physics and astrophysics, have been produced in proton-induced fission of 238 U and ionized in a laser ion guide coupled to an on-line mass separator. Their b decay was studied by means of b-g and g-g spectroscopy. Half-lives have been determined and production cross sections extracted. A partial level scheme is presented for 73 Cu and additional levels for 71 Cu, providing evidence for a sharply lowered position of the p1f 5͞2 orbital as occupancy of the n1g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 25 publications
(20 reference statements)
4
113
2
Order By: Relevance
“…Blocking cross-shell excitations above Z ¼ 28 inaccurately described the 1=2 − state systematics and the 71;73 Cu magnetic moments [10,11], whereas allowing proton excitations from the f 7=2 level gave a good description of the evolution of the 1=2 − state with N [12]. Similar conclusions resulted from the Coulomb-excitation study of the neighboring zinc isotopes: with an inert…”
supporting
confidence: 64%
“…Blocking cross-shell excitations above Z ¼ 28 inaccurately described the 1=2 − state systematics and the 71;73 Cu magnetic moments [10,11], whereas allowing proton excitations from the f 7=2 level gave a good description of the evolution of the 1=2 − state with N [12]. Similar conclusions resulted from the Coulomb-excitation study of the neighboring zinc isotopes: with an inert…”
supporting
confidence: 64%
“…spin I ¼ 3=2 for all odd-A Ga isotopes. However, in the Cu isotones with two protons fewer, it has been demonstrated that the proton SP ordering changes when neutrons start occupying the g 9=2 orbital around N ¼ 40 [5][6][7][8][9][10][11][12][13][14][15]. An inversion of the p 3=2 and f 5=2 SP levels was established recently in 75 Cu at N ¼ 46 [11], where the 5=2 À g.s.…”
mentioning
confidence: 99%
“…This region presents a key proving ground for the latest shell-model interactions, since it offers an attractively simple structure of the excited states in terms of particle-particle or particle-hole couplings. A compelling question in this region is related to the rapid reduction in energy of the 5/2 − state as the νg 9/2 orbital is filled in the Cu isotopes [1,2]. Given that this state remains static at approximately 1 MeV as neutrons fill the fp shell, its abrupt change at N = 40 garnered a great deal of interest and motivated further experimental and theoretical attention [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%